Відповідь:
x = -2 + √3 та x = -2 - √3.
Пояснення:
4x² + 9x - 3 - x = 2x² - 5
4x² + 9x - 3 - x - 2x² + 5 = 0
(4x² - 2x²) + (9x - x) + (5 - 3) = 0
2x² + 8x + 2 = 0
x² + 4x + 1 = 0
x = (-b ± √(b² - 4ac)) / (2a)
x = (-4 ± √(4² - 4 * 1 * 1)) / (2 * 1)
x = (-4 ± √(16 - 4)) / 2
x = (-4 ± √12) / 2
x = (-4 ± 2√3) / 2
x = -2 ± √3
Відповідь:
x = -2 + √3 та x = -2 - √3.
Пояснення:
4x² + 9x - 3 - x = 2x² - 5
4x² + 9x - 3 - x - 2x² + 5 = 0
(4x² - 2x²) + (9x - x) + (5 - 3) = 0
2x² + 8x + 2 = 0
x² + 4x + 1 = 0
x = (-b ± √(b² - 4ac)) / (2a)
x = (-4 ± √(4² - 4 * 1 * 1)) / (2 * 1)
x = (-4 ± √(16 - 4)) / 2
x = (-4 ± √12) / 2
x = (-4 ± 2√3) / 2
x = -2 ± √3
x = -2 + √3 та x = -2 - √3.